The acquisition of referring expressions a dialogical approach - Salazar Orvig, Anne, 1953-; Weck, Geneviève de; Hassan, Rouba; Rialland, Annie (Trends in language acquisition research ;, 2021)
"This book describes the repertoire and uses of referring expressions by French-speaking children and their interlocutors in naturally occurring dialogues at home and at school, in a wide-range of communicative situations and activities. Through the lens of an interactionist and dialogical perspective, it highlights the interaction between the formal aspects of the acquisition of grammatical morphemes, the discourse-pragmatic dimension, and socio-discursive, interactional and dialogical factors. Drawing on this multidimensional theoretical and methodological framework, the first part of the book deals with the relation between reference and grammar, while the second part is devoted to the role of the communicative experience. Progressively, a set of arguments is brought out in favor of a dialogical and interactionist account of children's referential development. This theoretical stance is further discussed in relation to other approaches of reference acquisition. Thus, this volume provides researchers and students with new perspectives and methods for the study of referring expressions in children"--